Menelisik Sumbangan Islam Bagi Peradaban Modern - Wahyudin Noor (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2017)
Islamic contributions to modern civilization, include: first, the contribution of Islam in modern science in a system of belief based on monotheism; secondly, in the political sphere, that Islam and democracy are essentially compatible, viable, and should be seen as a continuation or development of the Islamic "democratic" model; thirdly, for Islamic economics, starting from pioneering thinking to the continued to application of the system as part of the economic development of Islamic contributions to modern civilization; fourth, for social issues divided over human rights and women's status in Islam it opens up a golden opportunity for the Muslim community to radically revise the whole system of traditional thought toward a new system of thought, both in the Islamic horizon and the historical horizon of comparison; comparisons between Islam, Christianity, and Judaism, and specifically the comparison between Islam and modern Western achievements to the present day.